Agency within Mobility: Conceptualising the Geopolitics of Migration Management. Issue 4 (8th August 2022) - Borrelli, Lisa; Pinkerton, Patrick; Safouane, Hamza; Jünemann, Annette; Göttsche, Sandra; Scheel, Stephan; Oelgemöller, Christina
ABSTRACT: The movement of people across borders, and the varied governmental responses to that movement, is of crucial importance to contemporary geopolitics. Agency and mobility are two central themes in these debates. This Forum makes an intervention into such debates, by contributing to the conceptualisation of agency as a co-constitutive phenomena, and seeking a collaborative response to the question of how to rethink the paradigm of political agency. Within the diverse situations described in the Forum, the contributors trace the different ways in which migrant individuals enact and claim agency within the systems they encounter. While engaging with different case studies (migration to Germany, the UK, the EU and Japan; migration from and within West Africa) and utilising different methodologies (interviews, ethnographic research, policy analysis), the contributions are united by a determination to develop understandings of migrant and refugee agency that do justice to the complexity of the geopolitical situations in which persons find themselves: whether that is the inequalities produced by long-term factors such as colonialism and developmental interventions; or the contemporary cross-border movements driven by conflicts or regional, national and local circumstance. By recognising the various ways in which migrants, as political actors in their own right, engage with multiple forms of governance and management, we engage in a cumulative effort to make conceptual strides on the back of empirical research, in order to generate new avenues for productive research into the geopolitics of migration management.